Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz według wzoru a) (4∙3/5)(-4)*4^6*(3/5)^3=4.63 gwiazdek na podstawie 8 opinii

Oblicz według wzoru a) (4∙3/5)(-4)*4^6*(3/5)^3=

20Zadanie
21Zadanie
22Zadanie
23Zadanie

`a) \ \ (4*3/5)^(-4)*4^6*(3/5)^3=4^(-4)*(3/5)^(-4)*4^6*(3/5)^3=4^(-4+6)*(3/5)^(-4+3)=`

`=4^2*(3/5)^(-1)=16*5/3=80/3=26 2/3`

`b) \ \ (12*0,7)^(-3)/(12^(-4)*0,7^(-5))=(12^(-3)*0,7^(-3))/(12^(-4)*0,7^(-5))=``12^(-3)/12^(-4)*0,7^(-3)/0,7^(-5)=12^(-3):12^(-4)*0,7^(-3):0,7^(-5)=`

`=12^(-3-(-4))*0,7^(-3-(-5))=12^(-3+4)*0,7^(-3+5)=12^1*0,7^2=12*(7/10)^2=`

`=12*49/100=588/100=5 88/100`